Grammar from and function 3 - Broukal, Milada (Glencoe/McGraw-Hill, 2005)
In "Grammar Form and Function", high-interest photos provide a visual context within the grammar charts for learning and retaining new vocabulary and grammar. Flexible approach to grammar instruction integrates study of new structures (form) with information on how to use them and what they mean (function). High-interest photos contextualize new grammar and vocabulary and reinforce student recall. Comprehensive grammar coverage ensures thorough and effective presentation of all basic structures. Extensive practice guides students to accurate production and fluent use of new grammar. Your Turn Activities encourage students to draw from personal experiences and practice grammar in natural conversations. Writing Assignments incorporate grammar into step-by-step tasks for a variety of writing purposes, such as narrating and describing. Self-Tests and Unit Quizzes offer multiple assessment tools in both print and Web formats. Companion Website activities develop real-world listening skills.